Calcium-Alginate Gel Bead Cross-Linked with Gelatin as Microcarrier for Anchorage-Dependent Cell Culture - Young Jik Kwon; Ching-An Peng (BioTechniques)
Valuable products obtained from the cultivation of anchorage-dependent mammalian cells require large-scale processes to obtain commercially useful quantities. It is generally accepted that suspension culture is the ideal mode of operation. Because anchorage-dependent cells need surfaces to be able to attach and spread, the incorporation of microcarriers to suspension culture is indispensable. Since the dextran-based microcarrier was first introduced, many different types of microcarriers have been developed and commercialized. In this study, alginate-based microcarriers were made in the following order: (i) calcium-alginate gel beads prepared by dropping a blend of sodium alginate and propylene glycol alginate (PGA) into calcium chloride solution, (ii) the PGA section of gel beads cross-linked with gelatin in alkaline solution (i.e., via the transacylation reaction between the ester group of PGA and amino group of gelatin), and (iii) gelatin membrane around the beads further cross-linked by glutaraldehyde. The glutaraldehyde-treated gelatintransacylated PGA/alginate microcarrier showed superior features in high stability under phosphate-containing solution, density close to that of culture medium, and transparency. Moreover, the Chinese hamster ovary CHO-K1 and amphotropic retrovirus producer PA317 cells cultivated on the newly synthesized microcarriers exhibited similar growth kinetics of these two types of cell lines cultured on commercial polystyrene microcarriers. However, cell morphology was easily monitored on the transparent microcarriers made in this study.